(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study the possibilities for several kinds of topological, locally linear cyclic group actions of non-prime order on some closed, simply connected 4-manifolds with indefinite intersection form. Especially, we discuss the existence of locally linear pseudofree C_9 action on this kind of 4-manifolds.